FIQIH EUTHANASIA (PASSIVE EUTHANASIA PERSPECTIVE OF MASLAHAH MURSALAH FOR THE ACHIEVEMENT OF ASY-SHARI'AH MAQASHID) - Muhammad Zamroni (Universitas Islam Negeri Mataram, 2021)
Euthanasia case is a new case that often occurs in the middle of the Indonesian people, but sometimes people are not aware of it. This action is an act of euthanasia to hasten death in order to attain the good of the patients and their families. An action that is obtained from a physician diagnoses a patient who claims there is no hope for recovery and even life. Despite treatment, efforts continue to be made by the hospital, but that didn't produce results. Seeing the euthanasia case, researchers feel motivated to examine this case using the approach mashlahah mursalah to achieve maqhashidu ash-Shari'ah. One of the arguments used mashdar (source) within dig Islamic law.